(untitled) (Pedagogy of Higher and Secondary Education, 2013)
Rakityanskaya L. N. Scientific and pedagogical thought about the relationship of moral and aesthetic. The article analyzes the scientific and pedagogical views of philosophers and educators to the problem of the relationship of moral and aesthetic and the role of musical art in the moral and aesthetic education.